Detection of human papillomavirus distinguishes second primary tumors from lung metastases in patients with squamous cell carcinoma of the cervix. Issue 8 (3rd July 2020) - Lin, Suxia; Zhang, Xinke; Li, Xiaoxuan; Qin, Changfei; Zhang, Lihong; Lu, Jiabin; Chen, Qunxi; Jin, Jietian; Wang, Taoli; Wang, Fang; Zang, Shengbing
Abstract: Background: In patients with squamous cell carcinoma of the cervix (SCCC), a squamous cell carcinoma (SqCC) in the lung represents either a second primary tumor or metastasis. This distinction between second primary tumors and lung metastases in patients with SCCC significantly influences patient prognosis and therapy. Here, we aimed to differentiate second primary tumors from lung metastases in patients with SCCC by exploring the HPV status in SqCCs involving the lung within a large cohort. Methods: P16 expression was assessed using immunohistochemistry on tissue microarrays including a total of 415 primary lung SqCCs and 21 lung SqCCs with prior SCCC. Following this, we performed HPV DNA typing and the sensitive RNAscope in situ method to screen all the cases for HPV E6/E7 expression, which is a more reliable indicator of transcriptively active HPV in tumor cells. Results: The p16 positive expression rate was 13.7% (57/415) in primary lung SqCCs, but HPV DNA was not detected in any of the 57 primary lung SqCC cases that positively expressed p16. In contrast, HPV DNA was detected in all cases (21/21) with prior SCCC. Consistently, all 21 lung SqCCs with prior SCCC (21/21) showed extensive HPV16 E6/E7 expression. In striking contrast, none of the primary lung SqCCs (0/415) had a detectable RNAscope signal. Conclusions: HPV does not seem to play a role in the development of primary lung SqCCs. HPV detection may be helpful in distinguishing second primary tumors from lung metastases in patients with SCCC. Abstract : HPV does not seem to play a role in the development of primary lung SqCCs. HPV detection may be helpful in distinguishing second primary tumors from lung metastases in patients with SCCC.